Developing Human Resource Management IN Increasing Sustainable Competitive Advantage IN SMAN 4 Bekasi Student - Ahdi Mualim; Dwi Budi Srisulistiowati; Sri Rejeki; Sarfilianty Anggiani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Human Resources (HR) is a key component and determinant of success and failure in an organization or institution. Educational institutions are in dire need of talented people to help them succeed and achieve their goals. HR is the driving force behind the system and all facilities, assets, curriculum, facilities, infrastructure, and all other resources. All educational resources cannot function optimally if they are not supported by the availability of human resources, and should carry out strategic, integrated, cohesive, and comprehensive workforce planning for education personnel. This study uses the library research method, namely by collecting relevant data from books, journals, magazines, and so on. This type of research is qualitative research with a descriptive analysis method, namely a method that seeks to systematically present the material to obtain the results as a conclusion. Qualitative research is the process of exploring and understanding the behavior of individuals or groups. Describing social problems or humanitarian problems. This study uses the observation method by directly observing the activities carried out by students of SMA Negeri 4 Bekasi City. Education Personnel Planning provides direction for all institutions in terms of human resources needed, and human resource activities to be managed and developed, and can improve the effectiveness and efficiency of institutions, educators and education personnel can integrate with short-term planning goals and long-term educational institutions.